Toxicity of chloroform extracts of Derris indica Bennet. against Callosobruchus maculatus (F.) adults (University Journal of Zoology, Rajshahi University, 2009)
No Abstract Key words: Toxicity, Derris indica, Chloroform extract, Callosobruchus maculatus doi:10.3329/ujzru.v27i0.1963 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 95-96